ANALYSIS OF ONOMATOPOEIA IN KUNG FU PANDA 2 MOVIE BY USING NVIVO - Umratul Janah; Indra Perdana (Intensive Journal, 2022)
This study was aimed at determining: (1) the types of onomatopoeia by using NVivo, (2) the mimetic meanings classification of onomatopoeia by using NVivo (3) the English to Indonesian onomatopoeia translations in contextual meaning and their icon, index, and symbol of both languages used in Kung Fu Panda 2 Movie by using NVivo.This research is a descriptive study with a qualitative approach because the main purpose of this study is to find out the facts or descriptions of the onomatopoeia by using an application named NVivo. Contents analysis is a type of research because this research is centered on certain content or movie characteristics. The application helps analysis become more organize, analyze and visualize and unstructured information by providing tools for classifying, sorting and arranging data in ways that enable the identification of themes and patterns. The main data sources are all collected from movie scenes containing English onomatopoeia and supporting sources are from Indonesian onomatopoeia, both native speakers and other literature. As a result of research shows that the origin of 46 onomatopoeia: First, all types can be found in the film either they are lexical and non-lexical or personal, associative, but example. Likewise, all the structured divisions regarding the meaning of mimesis can be found, they namely phonomimetics, phenomimetics, psychomimetics, phonomimetics & phenomimetics, and phenomimetics & psychomimetics. Lastly, provide that English as well as Indonesian is iconic and symbolic, nothing indexical. Besides, that to obtained from asynchronous angles as follows:(a) a few onomatopoeia can be natural and lexical derivation, (b) one onomatopoeia can convey more than one mimetic meaning classification, (c) one onomatopoeia can be characterized for more than one marker foundation, (d) sound symbolism is implemented, (e) maximum onomatopoeia are monosyllabic, only few have 2 phrases each reduplication, and (f) it's far proven that the origin of each languages have total identical, almost equal, very distinct, and completely distinctive.